Corneal endothelial cell reduction and increased Neurokinin-1 receptor expression in a graft-versus-host disease preclinical model. (July 2022) - Bonelli, Filippo; Lasagni Vitar, Romina Mayra; Merlo Pich, Francesco Giorgio; Fonteyne, Philippe; Rama, Paolo; Mondino, Anna; Ferrari, Giulio
Abstract: The aim of this work was to assess corneal endothelial morphology in a well-established acute graft-versus-host disease (GVHD) murine model and to quantify the expression of neurokinin-1 receptor (NK1R) in the corneal endothelium during ocular GVHD (oGVHD). Pre-conditioning was performed in BALB/c using myeloablative total body irradiation. Subsequently, allogeneic bone marrow transplantation was performed without (BM) or with mature T cells (BM + T). Corneal transparency was monitored with in vivo biomicroscopy. After sacrifice, corneal thickness and endothelial cell number were measured, and the expression of NK1R was investigated in the corneal endothelium through immunofluorescence and quantified by immunohistochemistry. Mice presenting oGVHD showed a significant reduction in endothelial cell number compared to control animals (p < 0.0001). NK1R expression was significantly increased in oGVHD mice endothelium (p < 0.05). Corneal transparency and thickness were unchanged in all groups. Our results suggest that oGVHD affects the corneal endothelium, inducing a reduction of the cell number, and that this is associated with increased expression of the pro-inflammatory marker NK1R.